FEATURES OF MIGRATION OF HEAVY METALS IN THE NORTHERN CASPIAN ECOSYSTEM - Е. V. Chujko; A. S. Аbdusamadov (Юг России: экология, развитие, 2014)
Abstract. Aim. Study of the forms of migration of heavy metals in water of the Northern part of the Caspian Sea, the characteristics of their accumulation in sediments and fish fauna are presented.Methods. The western part of the North Caspian Sea is investigated in 2002–2009. Complex of sampling, transportation, storage and handling of samples was carried out in accordance with the regulations and methods of measurement.Results. The main share of elements in sea water was transferred as a part of suspended particles. Most often ionic forms of migration of metals dominated over weighed in the central part of a shallow zone of pre-mouth of Volga River. The greatest number of cases of excess was recorded by metals of maximum-permissible concentration in the central part of the studied water area with depths from 5 m to 10 m. It is established that the index of impurity of waters of the changed in the range from 0,2 (waters alone) to 3,4 (the polluted waters). The surface water of the water area is located in the western part of the studied area. The greatest coefficients of ground accumulation (CGA) are characteristic for iron and the manganese, the least for Zincum. The western part of the studied water area belongs to areas with the greatest values of CGA of metals in the north part of the Caspian Sea: zone near Island Chechen and the region of Volga-Caspian Channel. Cases of excess of the admissible residual concentration for lead and cadmium are noted in Neogobius fluviatilis and sprat ordinary practically in 50 % of cases, and in 35 % in Rutilus caspicus. Most often all studied hydrobionts containing metals in concentration above admissible residual concentration were met in zone before mouth of Volga River.Main conclusions. The main form of migration of heavy metals in the water of the north part of the Caspian Sea is suspension. The largest accumulation of heavy metals was found in the sediments of the western part of the area. The content of heavy metals in fish reflects their accumulation in sediments.